A phase 1, randomized, dose‐ranging study of GS‐5816, a once‐daily NS5A inhibitor, in patients with genotype 1–4 hepatitis C virus. Issue 12 (16th July 2015) - Lawitz, E.; Freilich, B.; Link, J.; German, P.; Mo, H.; Han, L.; Brainard, D. M.; McNally, J.; Marbury, T.; Rodriguez‐Torres, M.
Summary GS‐5816 is an inhibitor of the hepatitis C virus (HCV) NS5A protein that has demonstrated pan‐genotypic activity and a high barrier to resistance in HCV replicon assays. The aim of this study was to evaluate the safety, antiviral activity and pharmacokinetics of once‐daily doses of GS‐5816 in patients with genotype 1–4 HCV infection. Patients with genotype 1–4 HCV infection were randomized to 3 days of GS‐5816 at doses ranging from 5 to 150 mg or placebo. Adverse events were recorded, and plasma samples obtained for analysis of pharmacokinetics, HCV RNA and NS5A sequencing studies. GS‐5816 5–150 mg for 3 days was well tolerated and resulted in rapid declines in HCV RNA that were sustained over the dosing period. In patients treated with the 150 mg dose of GS‐5816, the mean maximal HCV RNA declines were 4.0, 4.0, 4.4, 3.3 and 3.5 log10 IU/mL in patients with genotype 1a, 1b, 2, 3 and 4 HCV infection, respectively. Pretreatment NS5A resistance‐associated polymorphisms were detected in 31% (22/70) of patients. Genotype 1 and 3 HCV‐infected patients without pretreatment NS5A resistance‐associated polymorphisms had greater declines in HCV RNA than patients with resistance‐associated polymorphisms. Plasma pharmacokinetics were supportive of once‐daily dosing. GS‐5816 demonstrated pangenotypic antiviral activity in patients with genotype 1‐4 HCV infection. It will be further evaluated in combination with other pangenotypic direct‐acting antivirals to achieve the goal of developing a well‐tolerated, highly effective treatment for all HCV genotypes.